A Performance Audit of First 30 Months of Manochaitanya Programme at Secondary Care Level of Karnataka, India - Agarwal, Preeti Pansari (Indian J Community Med, 2019)
INTRODUCTION: Lifetime prevalence of psychiatric disorders in India is about 14%, and the treatment gap is huge necessitating large-scale public health efforts. Manochaitanya programme (MCP), one such innovative program, was launched by the Government of Karnataka in October 2014. MCP entails provision of outpatient psychiatric care in subdistrict (Taluk) hospitals and primary health centers under a public–private (Indian Psychiatric Society-Karnataka chapter) partnership model, at least one Tuesday of every month. AIM: The aim was to do a secondary care level performance audit of MCP of initial 2½ years at all Taluka general hospitals of Karnataka. METHODOLOGY: Data on MCP were collected and tabulated from all 31 districts using a specially designed semistructured pro forma. This includes the number of self-reported psychiatric consultations in each Tuesday's clinic, number of psychiatrists, and their visit details. Prospective data were obtained from monthly reports. RESULTS: The district coverage was 100% during initial 2½ years over this period, i.e., MCPs were successfully covered in at least one Taluka hospital in all 31 districts. A total number of estimated consultations under this initiative were 73,663 with an average of 24.1 patients per psychiatrist consultation. One hundred and eleven psychiatrists participated in a total of 3,056 visits across the state. Patient footfall increased consistently over this time period. CONCLUSIONS: Psychiatrist-based Manochaitanya programme at secondary care level at Taluk hospitals has noticed substantial benefits to patient care. There is a need for psychiatrist-based secondary care at Talukas (subdistrict) level across the country.